2020
DOI: 10.1159/000505728
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgE Decision Point Cutoffs in Children with IgE-Mediated Wheat Allergy and a Review of the Literature

Abstract: <b><i>Background:</i></b> Wheat IgE-mediated food allergy in children is one of the most frequent food allergies in westernized countries, affecting between 0.4 and 1% of children. Although 95% predictive decision points have been determined for major allergens such as peanut, egg, and milk, the diagnostic performances of wheat-specific IgE (sIgE) and wheat component testing are not well established. <b><i>Objectives:</i></b> The aim of this study was to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…According to some studies, the cut-off level of 0.35 kUa/L for allergen-specific IgE might be insufficient to predict clinical reactivity [18][19][20][21][22]. For example, in the study by Garcia-Ara et al, it was shown that different cut-off points for specific IgE levels for milk and casein, which indicated clinical reactivity, were found at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…According to some studies, the cut-off level of 0.35 kUa/L for allergen-specific IgE might be insufficient to predict clinical reactivity [18][19][20][21][22]. For example, in the study by Garcia-Ara et al, it was shown that different cut-off points for specific IgE levels for milk and casein, which indicated clinical reactivity, were found at different ages.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of an adult population (median age 26 years) represents a strength, since, to our knowledge, this is the first study to have looked at the benefit of sIgE to tIgE ratio for the diagnosis of peanut allergy in this population. This provides data for clinicians who often apply pediatric data to their adult population since most literature discussing food allergy diagnosis is conducted in young pediatric populations with median ages ranging from 13 months to 10 years [3,5,6,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Specific IgE values can be influenced by multiple factors, including age and the presence of atopic dermatitis [2,3] and were also shown to correlate with total IgE levels [4], with a pediatric study demonstrating that the probability of having a positive OFC decreases when total IgE increases [5]. However, the benefit of sIgE to tIgE ratio in predicting OFC outcomes is inconsistent, with some pediatric studies supporting improved diagnostic accuracy [6,7] and others failing to show a benefit [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…We included 16 studies on accuracy of diagnostic tests for wheat allergy. For meta-analyses, there were 5 studies of SPT to wheat , 36,82,104,114,136,154,156,178 10 of sIgE to whe at 32,36,55,56,77,104,114,128,130,136,150,154,158,178 and 6 of ω-5 gliadin-sIgE 32,56,77,128,130,136 with pooled sensitivities of 53%, 72% and 79% and specificities of 72%, 79% and 78%, respectively (Table 2 and…”
Section: Wheat Allergymentioning
confidence: 99%